A Study on Nash-Collative Differential Game of N-Players for Counterterrorism - Mohamed Abd El-Hady Kassem; Abd El-Monem A. Megahed; Hebatallah K. Arafat (Journal of Function Spaces)
In this work, by using the Nash-collative approach for a differential game problem between N-governments and terrorist organizations, we study governments’ cooperation and the role of each government for counterterrorism. Furthermore, we discuss the intertemporal strategic interaction of governments and terrorist organizations, where all world governments have to cooperate to fight terrorism. Also, we study the necessary conditions for finding the optimal strategies for each government to fight terrorism; we discuss the existence of the solution of the formulated problem and the stability set of the first kind of the optimal strategies.